A DNN fingerprint for non-repudiable model ownership identification and piracy detection - Zheng, Yue (2022)
A high-performance Deep Neural Network (DNN) model is a valuable intellectual property (IP) since designing and training such a model from scratch is very costly. Model transfer learning, compression and retraining are commonly used by pirates to evade detection or even redeploy the pirated models for new applications without compromising performance. This paper presents a novel non-intrusive DNN IP fingerprinting method that can detect pirated models and provide a nonrepudiable and irrevocable ownership proof simultaneously. The fingerprint is derived from projecting a subset of front-layer weights onto a model owner identity defined random space to enable a distinguisher to differentiate pirated models that are used in the same application or retrained for a different task from originally designed DNN models. The proposed method generates compact and irrevocable fingerprints against model IP misappropriation and ownership fraud. It requires no retraining and makes no modification to the original model. The proposed fingerprinting method is evaluated on nine original DNN models trained on CIFAR-10, CIFAR-100, and ImageNet-10. It is demonstrated to have the highest discriminative power among existing fingerprinting methods in detecting pirated models deployed for the same and different applications, and fraudulent model IP ownership claims.